2014
DOI: 10.1590/1808-1657000172013
|View full text |Cite
|
Sign up to set email alerts
|

Ação repelente, inseticida e fagoinibidora de extratos de pimenta dedo-de-moça sobre o gorgulho do milho

Abstract: O objetivo deste trabalho foi avaliar o efeito repelente, inseticida e fagoinibidor de extratos de pimenta dedo-de-moça Capsicum baccatum (Willd.) Eshb. (Solanaceae) sobre o gorgulho do milho Sitophillus zeamais (Coleoptera: Curculionidae). O efeito repelente/atraente foi avaliado utilizando quatro arenas/repetições, nas quais foram adicionados os extratos vegetais nas concentrações 0; 2,5; 5; 10 e 20% e 140 insetos e, após 24 horas, efetuou-se a contagem de insetos. Para a atividade inseticida, em recipientes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
3
0
6
Order By: Relevance
“…Santos et al (2013) identified the presence of phenolic substances, such as flavonoids from the aqueous extract and ethyl acetate from the leaves of S. terebinthifolius. Whereas Guimarães et al (2014), evaluating the repellant, insecticide and fago inhibitor effect of the extracts of pepper dedo-de-moça (Capsicum baccatum) over corn Sitophilus zeamais weevil, found that the aqueous extract of seeds of pepper dedo-de-moça was the one that presented the greatest potential insecticide compared to the alcoholic extracts of 2.5, 5 and 10%. This corroborates the results observed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Santos et al (2013) identified the presence of phenolic substances, such as flavonoids from the aqueous extract and ethyl acetate from the leaves of S. terebinthifolius. Whereas Guimarães et al (2014), evaluating the repellant, insecticide and fago inhibitor effect of the extracts of pepper dedo-de-moça (Capsicum baccatum) over corn Sitophilus zeamais weevil, found that the aqueous extract of seeds of pepper dedo-de-moça was the one that presented the greatest potential insecticide compared to the alcoholic extracts of 2.5, 5 and 10%. This corroborates the results observed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…This percentage was lower in treatments #2 and #3 and showed a tendency of increase in treatment #4 -25% extract concentration (28% of insects attracted). Guimarães et al (2014) noticed that aqueous extracts from seeds of Capsicum baccatum showed repellent activity on maize weevils whereas the alcoholic extract from the pulp of Capsicum baccatum showed 34.6% attractiveness on adult Sitophilus zeamais insects. Such result is similar to those found in this experiment, which indicates that the substances released in alcohol might be different than those released in water.…”
Section: Resultsmentioning
confidence: 99%
“…De acordo com Costa et al (2009), as pimentas cumari, cambuci e malagueta podem ser usadas como conservantes naturais em alimentos, devido a presença de antioxidantes. Guimarães et al (2014) constata que extratos aquosos de sementes de pimenta dedo-de-moça apresentam atividade repelente sobre o gorgulho do milho e frutos de pimenta dedo-de-moça possuem atividade inseticida tanto na forma de extratos alcoólicos quanto de extratos aquosos. O uso de compostos bioativos de plantas no controle de pragas e vetores, por ser um método natural, torna-se mais seguro e barato do que a utilização de agroquímicos.…”
Section: Introductionunclassified